Knowledge of Early Childhood Education Teachers Regarding Zero Waste-Based Learning in the Coastal Area of Kamal - Tiara, Dinda Rizki; Pratiwi, Eriqa; Rizki Safira, Ajeng (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – This article aims to elucidate the knowledge of teachers in early childhood education institutions in the coastal area of Kamal regarding Zero Waste-based learning. Design/methods/approach – The research was conducted using a survey that focused on Zero Waste-based learning. Questionnaires were administered to 118 teachers in early childhood education institutions in the coastal area of Kamal. The data obtained were then analyzed using a one-sample t-test. Findings – The research findings indicate that the majority of teachers possess a high level of knowledge regarding Zero Waste-based learning. However, there is a minimal difference in the number of teachers with high and low levels of knowledge. Many teachers utilize recycled materials and natural resources for teaching materials. Research implications/limitations – This study can serve as a basis for providing training to early childhood education institutions, enabling them to improve Zero Waste-based learning and instill environmental consciousness in young children. Practical implications – This research highlights the need for collaboration between all parties involved in environmental sustainability and schools to enhance teachers' knowledge of appropriate environmental education for children. Ultimately, this can help children gain knowledge about the environment through specialized or integrated daily lessons. Originality/value –This study serve as a reminder to teachers in Kamal's coastal area to enhance their knowledge of Zero Waste as a tool for educating future generations of young children. Paper type Research paper